Keuntungan Pedangan Pengecer Sayur Kangkung di Pasar Wilken Tomohon Kecamatan Tomohon Timur Kota Tomohon - Walone, Anggelina; Talumingan, Celcius; Pangemanan, Lyndon Reinhardt Jacob (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to determine the profit of kale vegetable retailers in Wilken Tomohon Market, East Tomohon District, Tomohon City. This research was conducted for two months from June to July 2023 from the preparation stage to the preparation of research results located at Wilken Tomohon Market, East Tomohon District, Tomohon City. The data used in this research are primary data and secondary data. Primary data was obtained through interviews using a list of questions (questionnaires) to kale vegetable traders in Wilken Market, Tomohon City. Secondary data were obtained from available books, such as local books and the internet and accessing articles from various scientific journals. The sampling method was simple random sampling and a sample of 10 kale traders was taken. The research data analysis method is based on the data obtained, processed and tabulated in accordance with the results of the analysis, to test the data that has been collected in order to obtain the amount of profit, which is obtained through profit analysis. Based on the results of the study, it shows that the profit of kale vegetable retailers at Wilken Tomohon Market is obtained from total revenue of Rp1,142,000 per week less total costs of Rp703,020 per week, the profit of kale vegetable retailers is Rp438,980 per week.